Management of Chronic Hepatitis C in Cirrhosis and Liver Transplant Population - Habib, MD, Shahid; Shaikh, MD, Obaid Shakil (North American Journal of Medicine and Science, 2014)
Hepatitis C treatment has evolved tremendously since the discovery of the virus 24 years ago. Patients with cirrhosis, metabolic syndrome, co-infection with HIV, end stage renal disease and liver allograft recipients are particularly difficult to treat. At the same time, such patients often suffer from significant morbidity and mortality. This review primarily focuses on treatment of HCV infection in patients with cirrhosis and liver allograft recipients. First generation HCV protease inhibitors, boceprevir and telaprevir, improved sustained virologic response rates in both treatment naive and treatment experienced patients. However, both drugs are associated with significant adverse events and drug-drug interactions, thus limiting their use in patients with advanced liver disease and allograft recipients. The advent of highly effective and better tolerated oral anti-virals have dramatically enhanced treatment efficacy with response rates exceeding 90%. It is expected that such agents will significantly alter the outlook for difficult to treat HCV infected populations.